2013
DOI: 10.1007/s13139-013-0231-7
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Metabolic Heterogeneity for Prediction of Disease Progression After Concurrent Chemoradiotherapy in Patients with Inoperable Stage III Non-Small-Cell Lung Cancer

Abstract: Intratumoral metabolic heterogeneity of primary lung tumor in (18)F-FDG PET/CT can predict disease progression after CCRT in inoperable stage III NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 23 publications
(32 reference statements)
2
49
1
2
Order By: Relevance
“…Recently, studies have suggested that the examination of spatial heterogeneity with computed tomography (CT) and the use of SUVs within solid tumors (particularly NSCLC) may provide prognostic information (8)(9)(10)(11)(12). Although these studies have generated compelling early evidence that heterogeneous tumors may lead to inferior outcomes, they have lacked adjustment for known prognostic factors and the use of proper validation techniques.…”
Section: Nuclear Medicine: Stage III Non-small Cell Lung Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies have suggested that the examination of spatial heterogeneity with computed tomography (CT) and the use of SUVs within solid tumors (particularly NSCLC) may provide prognostic information (8)(9)(10)(11)(12). Although these studies have generated compelling early evidence that heterogeneous tumors may lead to inferior outcomes, they have lacked adjustment for known prognostic factors and the use of proper validation techniques.…”
Section: Nuclear Medicine: Stage III Non-small Cell Lung Cancermentioning
confidence: 99%
“…Pretreatment risk or prognosis in patients with NSCLC (9)(10)(11). It is hypothesized that tumor heterogeneity in fluorodeoxyglucose PET tracer uptake may reflect underlying tumor biology such as hypoxia, angiogenesis, and necrosis (21).…”
Section: Nuclear Medicine: Stage III Non-small Cell Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor heterogeneity measured by 18F-FDG PET/CT has been emphasized in various malignancies. Heterogeneity has been associated with treatment response in esophageal cancer and rectal cancer [8,9] and prediction of disease progression in lung cancer and nasopharyngeal carcinoma [10,11]. Other studies have suggested that tumor heterogeneity is associated with histopathological features in lung cancer, head and neck cancer, and oligodendrogliomas [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Simple product of volume and metabolic activity may not be the most accurate solution, and recently, a new metric was proposed that incorporates the commonly utilized metrics of SUV, metabolic tumor volume, and total lesion glycolysis into a single parameter [14]. Various textural features and parameters representing tumor heterogeneity have shown much potential for predicting disease progression [15,16]. How to best represent the volumetric and SUL data, and possibly such features as intratumoral metabolic heterogeneity, is a challenge that needs to be further investigated.…”
Section: Performing Percistmentioning
confidence: 99%